Social mobility in the slipstream: first-generation students' narratives of university participation and family. Issue 1 (2nd January 2021) - Wainwright, Emma; Watts, Mike
ABSTRACT: In recent years, increasing research attention has been devoted to "first-generation" or "first-in-family" university students. For a sizeable cohort of students there is still little or no family tradition of supporting new university entrants into, and few expectations of, the novel and unfamiliar territory of university life and work. Contextualised by UK policy concerns over limited widening participation and social mobility, we extend current research on first-generation university students with an enhanced focus on family and home. Drawing on extended narratives from eight first-generation students, this paper explores the extent to which these students can have a "slipstream" effect back upon the home, on their siblings and, in some instances, on their parents. Informed by understandings of family learning and social learning theory, the concept of familial role-modelling is used to consider the transmission of learning within the family. With familial cultures of learning a key driver for young people's ambitions and aspirations, by focusing on the under-researched links between home, family, and university, we stress the importance of further exploring the experiences of first-generation students. This, we argue, is necessary for individual universities, the HE sector, and government to better acknowledge and address.